Using economic prejudice in the resolution of tax disputes - Бєлкін, Леонід Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Based on the principle of unity of public and private law deals with the effective protection of rights and legal interests of business entities in Ukraine in the economic-administrative relations. It is shown that in the conditions in disregard of administrative activity of the presumption of legality principle agreement increasing the effectiveness of protection is achieved at the expense of creating a judicial economic prejudice. Thus, the Supreme Administrative Court of Ukraine (hereinafter – SACU) issued a letter of 02.06.2011 № 742/11/13-11 (hereinafter – the letter № 742/11/13-11), which reported that no tax relations can apply article 204 of the Civil Code of Ukraine, according to which the transaction is legitimate if its invalidity is not directly established by law or if it is not recognized by the court as invalid. Thus, SACU alone «canceled» Article 204 of the Civil Code regarding the presumption of legality of the transaction. «Denial» letter № 742/11/13-11 presumption of legality of the transaction is the need for more effective remedies contracts. One of these tools is a relatively judicial preclusion validity of contracts in the courts of another specialization – civil or economic. The method of business (Civil) preclusion is that in an environment where tax spontaneously recognize invalid, fictitious, worthless and so any contracts at their discretion, and administrative courts tax authorities in that condone should advance (although it is sometimes possible in during inspection) recognize valid contract or acknowledge delivery of the court – in economic or (rarely) the general court. The advantage of this approach is, first, a reverent attitude to the system of economic courts evidence of unlawful transaction. But the second and perhaps more important advantage is that formally considering purely economic relations, economic courts will not interfere in relations budget and not «solve» the issue of filling the budget. And the administrative courts, which in the sense of power, «responsible» for filling the budget simply have to reckon with the decision of (general) courts, because under Part. 1, Art. 72 of the Code of Administrative Procedure Ukraine, the circumstances established by the court decision in an administrative, civil or commercial matters, which came into force is not proved when considering other cases which involved the same person or persons against whom these circumstances. That is, there is risk diversification for administrative judges being branded an «enemy of the budget». Of course, direct recognition of the contract valid or finding of direct deliveries to Ukrainian commercial proceedings impossible. But perhaps in some instances to develop and implement specific legal structures that would achieve the desired objective. We give examples tested jurisprudence of such legal structures. So, based on the principle of unity of public and private law and given state-legal pressure on the entities proposed a set of measures aimed at the use of economic preyudytsiy with tax disputes, including through forced replacement of the presumption of legality of obtaining legal business transaction preyudytsiy. Generalized jurisprudence.